2017
DOI: 10.1089/jwh.2016.6249
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Nonparticipation and Dropout of Women in Cardiac Rehabilitation Programs: A Systematic Review

Abstract: Women reported multilevel barriers for nonparticipation in and dropout from CR programs. Future clinical guidelines should evaluate and eliminate these barriers to improve adherence to CR programs in women. In addition, understanding the barriers for nonparticipation and dropout may be beneficial for future intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 55 publications
2
90
0
Order By: Relevance
“…Two reviews found that CR completion was associated with individual and contextual factors such as the perceptions of CR programs, being male, younger than 65 and having transport [ 15 , 16 ]. Specifically in women, recent systematic reviews found that CR dropout is influenced by multilevel barriers such as intrapersonal barriers, interpersonal barriers, logistical barriers, health system barriers, or CR program barriers [ 17 19 ]. However, the only qualitative studies included in these reviews were related to experiences or reasons for women’s participation into CR [ 20 22 ], and there were no specific qualitative studies focused on women’s reasons for dropping out from CR.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews found that CR completion was associated with individual and contextual factors such as the perceptions of CR programs, being male, younger than 65 and having transport [ 15 , 16 ]. Specifically in women, recent systematic reviews found that CR dropout is influenced by multilevel barriers such as intrapersonal barriers, interpersonal barriers, logistical barriers, health system barriers, or CR program barriers [ 17 19 ]. However, the only qualitative studies included in these reviews were related to experiences or reasons for women’s participation into CR [ 20 22 ], and there were no specific qualitative studies focused on women’s reasons for dropping out from CR.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existing evidence, there is little development of hospital CR units in primary care environments (phase II of CR). [13][14][15][16][17][18][19]. For this reason, most patients are sent back home without a start-up program that advises them on their illnesses and the changes in habits that are fundamental for their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This phase has the peculiarity that the person may have already returned to his/her routine activities and/or to the workplace, and this phase extends in time for the rest of the patient's life cycle. [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…9 Women in this age group often have conflicting work or family responsibilities, making it difficult to schedule health care visits. 10 Therefore, a need exists for developing innovative educational strategies for women seeking menopause health information. 11 As defined by the Office of the National Coordinator for Health Information Technology, patient portals are secure online websites that give patients convenient 24-hour access to personal health information from anywhere with an Internet connection.…”
Section: Introductionmentioning
confidence: 99%